Perioperative Application of Transesophageal Echocardiography in Left Atrial Appendage Occlusion in an Elderly Patient with Mirror-Image Dextrocardia and Atrial Fibrillation - Lu Zhang; Ming Bai; Ji-zhe Xu; Ga-xue Jiang; Ai-yun Deng; Zheng Zhang (Case Reports in Cardiology)
Mirror-image dextrocardia is non-life-threatening but not commonly diagnosed in the clinic. With the internal organs reversed, most of the patients with mirror-image dextrocardia have no clinical symptoms if the dextrocardia is not combined with other intracardiac malformations. Mirror-image dextrocardia is often discovered during other physical check or performing other examinations. In the present study, we reported a successful closure of a left atrial appendage in an 84-year-old patient with mirror-image dextrocardia with atrial fibrillation under the guidance of transesophageal echocardiography (TEE). Detailed perioperative steps of patient procedure description and TEE monitoring were described in this report.